Cybersecurity in E-banking - Mala, Agnesa; Desku, Behrije Ramaj; Sadrija, Thëllëza Latifi (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
This study aims to analyze the challenges and defenses in e-banking cybersecurity. The main goal is to identify the most common threats, the factors that affect the success of attacks and the effectiveness of defenses implemented by financial institutions. This study is important for financial institutions and e-banking users, as it helps to raise awareness and develop better strategies for protecting financial data. To achieve this goal, a qualitative methodology was used with a purposeful selection of participants, including cybersecurity experts and representatives of the banking sector. The main data collection instruments were semi-structured interviews and literature review, providing a complete overview of the risks and defense strategies adopted. The findings have shown that phishing attacks, malware, DDoS and insider attacks are among the main threats facing e-banking systems. Technological measures, such as multi-factor authentication and real-time monitoring, have been identified as key strategies for protecting systems. Likewise, customer education and employee training are critical factors in minimizing risks. Improving IT infrastructure and adopting advanced technologies, such as artificial intelligence and block chain, are recommended to strengthen security in the global banking sector.